Developing and Evaluating a Project-Based Academic Vocabulary Flipbook Integrating Papuan Local Wisdom: Validity, Practicality, and Effectiveness - -, Heriyanti; Pasandalan, Sittie Noffaisah; Rahmawati, Fitria; Yuliana; Andini Putri Cahyani; Rumasukun, Halima (STAIN Majene, 2025)
Academic vocabulary is essential for university students’ success in scientific reading and writing, yet instructional approaches remain largely conventional and insufficiently connected from students’ cultural contexts. This study aimed to develop and evaluate a project‑based academic vocabulary flipbook integrating “Papuan local wisdom” for the English Education Study Program at Universitas Muhammadiyah Sorong. The flipbook was developed using the ADDIE model through needs and curriculum analysis, instructional design, multimedia content creation using “Canva”, “YouTube”, and “Heyzine”, limited implementation with 20 students, and expert as well as user evaluation. Data were collected via questionnaires, expert validation rubrics, interviews, and pre‑ and post‑tests, and were analyzed descriptively and using a paired‑sample t‑test. The findings show high validity, with subject matter experts assigning a mean of 3.85 (“excellent”) for content, and media experts 3.82 (“excellent”) for technical quality; students rated the flipbook “good” (mean 3.41) across instructional and technical aspects. For practicality, experts and students reported overall scores of 96.18%, 95.57%, and 84.94% (“very practical”). Pre‑ and post‑tests showed an average gain of 10.30 points (from 55.10 to 65.40) in academic vocabulary scores, with t(19) = ‑3.884, p = 0.001, indicating a significant improvement. Qualitative feedback highlighted the flipbook’s “clarity, engagement, and cultural relevance” and its role in helping students correctly use academic vocabulary in meaningful, project‑based contexts. In sum, the developed flipbook is valid, practical, and effective for enhancing academic vocabulary learning in a culturally responsive manner.